2023
DOI: 10.1145/3542946
|View full text |Cite
|
Sign up to set email alerts
|

iBiR : Bug-report-driven Fault Injection

Abstract: Much research on software engineering relies on experimental studies based on fault injection. Fault injection, however, is not often relevant to emulate real-world software faults since it “blindly” injects large numbers of faults. It remains indeed challenging to inject few but realistic faults that target a particular functionality in a program. In this work, we introduce iBiR , a fault injection tool that addresses this challenge by exploring change patterns associated to user-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Their results are promising, however, the fact that these techniques depend on the availability of numerous, diverse, comprehensive and untangled fix commits [27] of not coupled faults [43], which is often hard to fulfil in practice, may hinder their performance. Acknowledging for the injection location [13], [42], Khanfir et al [32] combined the usage of information retrieved from bug reports with inverted automated-program-repair patterns to replicate real faults fixable by the original fix-patterns. Their results showed that they can generate faults that mimic real ones, however, their approach remains dependent and limited to the presence of good bug reports.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results are promising, however, the fact that these techniques depend on the availability of numerous, diverse, comprehensive and untangled fix commits [27] of not coupled faults [43], which is often hard to fulfil in practice, may hinder their performance. Acknowledging for the injection location [13], [42], Khanfir et al [32] combined the usage of information retrieved from bug reports with inverted automated-program-repair patterns to replicate real faults fixable by the original fix-patterns. Their results showed that they can generate faults that mimic real ones, however, their approach remains dependent and limited to the presence of good bug reports.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, Mirshokraie et al [41] compute complexity metrics from program executions to extract loca-tions with good observability to mutate. Other approaches restrict the fault injection on specific locations of the program, such as the code impacted by the last commits [38], [58] for better usability in continuous integration, or targeting locations related to a given bug-report [32] to target a specific feature or behaviour, etc. More recent advances have resulted in powerful techniques for cost-effectively selecting mutants, i.e., by avoiding the analysis of redundant mutants (basically, equivalent and subsumed ones) [24], [25], [28].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The vulnerability intent is predefined rather than learnt as INT-JECT does. In contrast, IBIR exploits bug reports to identify source code locations to be made faulty and inverts program repair fixes to inject faults [13]. Notably, both BUG-INJECTOR and IBIR do not specifically target vulnerabilities.…”
Section: Limitations Of the State-of-the-artmentioning
confidence: 99%
“…Most approaches inject faults based on predefined syntactic transformation rules (aka mutation operators) [6], [18], such as replacing an instance of a relational operator with another operator, e.g., replacing > with >=. Other approaches aim at injecting faults by either following fault patterns created or learned from recurrent fault instances [29], [51], [48] or by employing code pretrained language models [19]. These approaches have been implemented and made openly available as tools, serving the main purposes of mutation testing -tests assessment and guidance criterion.…”
Section: Introductionmentioning
confidence: 99%